PENDAMPINGAN PENYUSUNAN PROPOSAL DANA INDONESIANA KATEGORI DUKUNGAN INSTITUSIONAL BAGI ORGANISASI KEBUDAYAAN PADA SANGGAR NGUDI ROSO DUSUN NGLURAH TAWANGMANGU JAWA TENGAH - Panjaitan, Ingrid; Damardjati, Fx; Martalia, Diana (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The purpose of this community service activity is to enhance the capacity of organizations in submitting effective funding proposals, strengthen their competitiveness in a tight competition, and improve the quality of the programs implemented. Many cultural organizations, especially those on a small scale, often lack sufficient experience or knowledge in crafting attractive and persuasive proposals. Through mentoring, Sanggar Ngudi Roso can learn to prepare realistic and transparent budgets, as well as understand how to link cultural programs with social responsibility values, build networks and collaborations, create opportunities, and formulate effective monitoring and evaluation strategies. With ongoing support, cultural organizations can continue to improve their ability to manage programs and submit proposals in the future, thereby contributing to the preservation and development of local culture.